2017
DOI: 10.1159/000475498
|View full text |Cite
|
Sign up to set email alerts
|

Use of Epinephrine in Patients with Drug-Induced Anaphylaxis: An Analysis of the Beijing Pharmacovigilance Database

Abstract: Background: Few studies assessing the use of epinephrine in drug-induced anaphylaxis (DIA) in the hospital setting are available. We utilized the Beijing Pharmacovigilance Database (BPD) to evaluate the appropriateness of epinephrine for DIA management. Methods: DIA cases collected in the BPD from January 2004 to December 2014 were adjudicated and analyzed for demographics, causative drugs, clinical signs, outcomes, initial treatment, route, dosing, and cardiovascular adverse events (CAE) of epinephrine. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…Using a structured database inquiry, extraction, and case adjudication methodology as reported in our previous study [ 10 ], we performed a detailed analysis on DIA cases. The cases were reported to the BPD from January 1, 2004 to December 31, 2014.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a structured database inquiry, extraction, and case adjudication methodology as reported in our previous study [ 10 ], we performed a detailed analysis on DIA cases. The cases were reported to the BPD from January 1, 2004 to December 31, 2014.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast with our previous study [ 10 ], anaphylaxis-inducing drugs were classified into various pharmacotherapeutic groups according to the Martindale—The Complete Drug Reference (37th edition) [ 11 ], World Health Organization (WHO) Model Formulary (2008) [ 12 ], and Chinese Pharmacopoeia (ChP) [ 13 ]. Within each group there were several subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, underuse, inappropriate IV bolus use, and overdose were identified as major problems with epinephrine use, emphasizing the importance of training for professionals and education for patients [100]. …”
Section: Identifying and Managing Anaphylaxismentioning
confidence: 99%
“…However, prevalent clinical practices with respect to emergency treatment of anaphylaxis in Chinese primary care units are not well identi ed. Limited studies found under-use and/or inappropriate use of epinephrine during treatment of anaphylaxis in China [4][5][6] , but all these studies were investigated in large hospitals in Beijing before the year of 2014; in addition, these reports did not provide speci c information about the critical initial treatment of anaphylaxis. Accordingly, we evaluated the actual emergency treatment of anaphylaxis initially treated in Chinese primary care units by analyzing published cases during period of 2014 to 2018.…”
Section: Introductionmentioning
confidence: 99%